2014
DOI: 10.5603/ait.2014.0002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of haemodynamics and myocardial injury markers under desflurane vs. propofol anaesthesia for off-pump coronary surgery. A prospective randomised trial

Abstract: Background: Several studies have highlighted that volatile anaesthetics improve myocardial protection in cardiopulmonary bypass coronary surgery. However, the haemodynamic effect of desflurane in off-pump coronary surgery has not been clarified yet. Our study hypothesis was that desflurane-fentanyl anaesthesia could decrease myocardial injury markers and improve haemodynamics compared to propofol-fentanyl in patients undergoing off-pump coronary surgery. Methods: Design: Prospective randomised open-label study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Sixteen trials included participants under 60 years of age [27,35,41,42,44,50,52,55,65,68,70,73,74,[77][78][79]. Five trials did not report the age of the participants [27,28,49,61,64]. Of the remaining trials, the mean age of the participants in each group trials ranged from 48.9 years to 76 years, with an average mean age for the groups of 63.7 years (range 50.0 to 75.0 years) ( Table 2).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen trials included participants under 60 years of age [27,35,41,42,44,50,52,55,65,68,70,73,74,[77][78][79]. Five trials did not report the age of the participants [27,28,49,61,64]. Of the remaining trials, the mean age of the participants in each group trials ranged from 48.9 years to 76 years, with an average mean age for the groups of 63.7 years (range 50.0 to 75.0 years) ( Table 2).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The overall methodological quality of the included studies was about evenly split between those in which the classification was unclear and those in which the studies were categorised as low risk of bias. Allocation concealment was a major risk of bias limitation in three trials [28,45,66] and blinding of participants and personnel and outcome assessors in eight [30,35,36,37,53,61,63,70].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Equal success has been achieved using both thoracic epidural anesthesia and general anesthesia techniques for OPCAB surgery (40,(47)(48)(49). OP-CAB with thoracic epidural anesthesia allows efficient cerebral blood flow management, reduces the rate of postoperative arrhythmias, and improves pain control with overall satisfactory recovery (45).…”
Section: Anesthetic Technique and Perioperative Challenges Of Opcabmentioning
confidence: 99%
“…The choice of general anesthetic agents has been variable, and many have claimed their unique aspect of advantage. Some studies have suggested that using inhalational anesthetic agents for OPCAB might decrease myocardial injury and accelerate recovery of myocardial contractility (49,50). On the other hand, many different types of total intravenous (IV) anesthesia medication, including propofol, have been utilized for OPCAB surgery (48,(51)(52)(53).…”
Section: Anesthetic Technique and Perioperative Challenges Of Opcabmentioning
confidence: 99%
“…Other authors on the contrary did not find differences in terms of troponin release when it was compared to a propofol group of patients [ 39 ]. Desflurane was reported to improve LSWI when compared to a propofol anesthetic regime, although no differences in troponin release were observed [ 40 ], and moreover was found to be less effective in reducing incidence of arrhythmias than sevoflurane [ 34 ]. Guarracino et al observed a significant reduction in troponin release in a cohort of 57 patients anesthetized with desflurane [ 41 ].…”
Section: Reviewmentioning
confidence: 99%